Influence Of Personality Traits On Students’ Academic Achievement In Secondary Schools In Harari, Eastern Ethiopia - Sakata, Moti Gelata; Gobena, Gemechu Abera; Dilgasa, Geleta Sitota (Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
This study investigated the influence of personality traits on the academic achievement of the Secondary School at Harari, Eastern Ethiopia. This study used the explanatory sequential mixed method design using a standardized instrument as a primary data-gathering tool. The study's respondents were students from four secondary schools in Harari State (N = 347), who were selected using the stratified random sampling technique. The study found that Conscientiousness (r=0.46, p<0.05) was significantly positively related to academic achievement, whereas Neuroticism (r=-0.39, p<0.05) was significantly negatively related to academic achievement. Results from regression analysis showed that Conscientiousness was the strongest predictor of academic achievement. In conclusion, personality traits significantly affect students’ academic achievement. This study suggests that teachers, parents, and students should be educated on the knowledge that personality traits play a major role in academic activities and performance.